AKUNTABILITAS BIAYA PENDIDIKAN DI MARKAZUL QURAN BUKITINGGI - Rio Friyadi; Hamdi Abdul Karim (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Quality education certainly requires efficient and accountable financial management in educational institutions. This research provides an in-depth review of the role of accountability in education financing at Markazul Quran Bukitinggi. This research method uses descriptive qualitative with a case study approach, data collection techniques include interviews. This research includes the mechanisms implemented in building accountability for education costs. Markazul Quran Bukitinggi in preparing, implementing and evaluating their financial accountability system. also highlights the important function of transparency in building the trust of stakeholders, including parents, teachers and the community. The aim of this research is to provide valuable insights for education stakeholders in a formal or non-formal educational institution, helping to understand how important financial accountability and transparency are in achieving sustainable and quality education goals.